Profile of para athletes and characterization of sports injuries during the 2023 Paralympic School Games - Ana Flávia Medeiros Ribeiro; Renato de Souza Melo; Daniela Cristina Rodrigues Carvalho; Juliana Fernandes; Saulo Fernandes Melo de Oliveira; Rafaella de Andrade Monteiro; Andressa da Silva de Mello; Caroline de Cássia Batista de Souza; Maria Julia de Lyra Cardoso; Maria Das Graças Rodrigues de Araújo; Ana Paula de Lima Ferreira (International Biomechanics, 2025)
This article explores the characterization of sports injuries among young athletes participating in the 2023 Paralympic School Games. Injuries during the physiological growth phase can not only compromise the development of sports skills but also harm the physical development expected for their age group. Adaptive mechanisms to training are the main determinants of the location of injuries, traumas and musculoskeletal complaints. This paper aimed to identify occurrence of sports injuries in para athletes during the 2023 School Paralympics. The study population consisted of students who participated in the national stage of the 2023 School Paralympics, held at the Paralympic Training Center in the state of São Paulo. The sample consisted of 640 para-athletes, 253 (60.5%) females and 387 (60.5%) males, with an average age of 14.06 years. Overall, 14.9% of the participants reported injuries/illness. The team with the highest percentage of injured members was from the state of Tocantins (14.8%). Most of the injured athletes had intellectual disabilities (41.46%), practiced athletics (56.9%) and were in the final years of elementary school (21.95%), with an average age of 14.56 years, and the majority were male (56.86%).